Comportamiento del cultivo del ajonjolí bajo diferentes densidades de población en la granja Santa Inés - Sánchez Cedeño, Zaida Sabrina (2018)
The densities are fundamental for a good population with their respective distances between their rows and furrows to obtain an excellent crop and good productivity, thus generating profits without losses. In these times a good production of the crop generates good food One of the most characteristic uses of this crop is in the gastronomic area, it has high protein seeds to be consumed, it must be toasted and crushed so that it can benefit otherwise the organism expels it without digesting . Some inhabitants lack adequate food due to lack of economy. It is easy to manage since it is tolerant to drought, it grows in most of the frank and well drained soils, it can usually be planted to heavy or sandy soils and several agroclimatic regions, adapted to different rotations. Seed production yields under conditions, high temperatures and can grow in soil moisture stored without rain and irrigation. It adapts to low areas 0-8000 meters, to floors of The cultivation of sesame is an oilseed, these plants cover very important crops, are plants with seeds that can extract oils and are used mostly in industry, has a harvested world area 1,877,172 ha and a production 4,586,060 tons of seeds.Great importance for its seeds that are very nutritious that provide oils. It has a facility in the production of green lubricants unlike other vegetable oils. The objective of the research was to evaluate the effect of population density on the agronomic behavior of the sesame crop in the farm Santa Inés, Academic Unit of Agricultural Sciences belonging to the Technical University of Machala province of El Oro. Four treatments were used to evaluate distances from; (0.60x0.15) (0.60x0.20) (0.60x0.25) (0.60x0.35) with their respective replicates that were randomized in the experimental units within each row and within each column using the simple Latin square design, because the work area presents two factors that are not controlled, such as soil fertility and slope of the ground, which will reduce the experimental error that may be generated in the data. Variables were used in the vegetative and productive cycle: height of silver at 60 days and at harvest, number of capsules and seeds, weight of 100 seeds and the total yield of the crop to determine which of the treatments can be applied generating greater production in the agricultural field. In all the cases evaluated, it indicates that treatment 4 (0.60cmx0.30cm) achieves the best life cycle of the crop with high yield, a value which is statistically different with the others. So it is evident that a reduction in planting density influences the development of the crop and therefore an impact on yield is generated as is the case of treatment 1 (0.60cmx0.15 cm) that showed the low variables that may be conditioned to the competition the cultivation of water, nutrients, little sunlight, greater number of weeds. It is evident that in the treatments applied as the distance increases, it reaches its best performance.